Anaglyph Caustics with Motion Parallax. (27th October 2016) - Lancelle, M.; Martin, T.; Solenthaler, B.; Gross, M.
Abstract: In this paper we present a method to model and simulate a lens such that its caustic reveals a stereoscopic 3D image when viewed through anaglyph glasses. By interpreting lens dispersion as stereoscopic disparity, our method optimizes the shape and arrangement of prisms constituting the lens, such that the resulting anaglyph caustic corresponds to a given input image defined by intensities and disparities. In addition, a slight change of the lens' distance to the screen causes a 3D parallax effect that can also be perceived without glasses. Our proposed relaxation method carefully balances the resulting pixel intensity and disparity error, while taking the subsequent physical fabrication process into account. We demonstrate our method on a representative set of input images and evaluate the anaglyph caustics using multi‐spectral photon tracing. We further show the fabrication of prototype lenses with a laser cutter as a proof of concept.